HEALTH MONITORING OF STRUCTURAL ELEMENTS USING CT-XRAY - F. Nateghi Alahi; S.S. Kamali (مهندسی عمران شریف)
Structural health monitoring is becoming more reliable as technology advances. Many structures are in use throughout cities and environments that require constant attention due to fatigue of corrosion and environmental effects such as floods, earthquakes, or strong winds. This means that with the advent of new damage detection techniques, authorities can make sure that these vital structural elements, such as road signs or traffic lights and so on, are safe. The important key to these techniques is that they must be simple and relatively inexpensive. Therefore, an attempt was made to use techniques in medical practice and adapt those to structural members. In this article, the effectiveness of X-ray computed tomography in the inspection of urban structures and building structures is discussed. X-ray tomography is a non-destructive method based on X-ray absorption, widely used in the medical field. By using this method, it is possible to study and examine the internal structure of old structures to fix defects and maintain the safety of residents, as well as to maintain them as best as possible. For example, urban structures such as electric poles and traffic signs cause financial losses or even deaths due to natural hazards or wear and tear every year. One of the features of this method is its high accuracy and speed in checking the member. Considering the capabilities of this method, in this research, a baggage inspection device at the MehrAbad airport was used to examine a number of concrete and wooden samples to identify defects such as cracks, holes, or knots in wooden samples. The investigation results are directly related to the device's power and the duration of radiation used on the sample. According to the results, defects such as cracks in concrete or knots in wood can be observed.